2008
DOI: 10.1002/ajmg.b.30833
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in the serotonin 2A receptor and suicidal ideation in a sample of 270 Irish high‐density schizophrenia families

Abstract: Genetic variation in the serotonin 2A receptor (HTR2A) has been associated with both schizophrenia and suicidal behavior. Our sample comprised 270 Irish high-density schizophrenia families (n=1408 subjects, including 755 with psychotic illness). Diagnoses were generated using a modified SCID. All patients who had at least one episode of psychosis were rated on the Operation Criteria Checklist for Psychotic Illness (OPCRIT). Lifetime history of suicidal ideation was determined from medical records and psychiatr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 45 publications
1
9
0
1
Order By: Relevance
“…Analysis of the 5-HTR1A rs6295 variant produced no association with suicidal behaviour (González-Castro et al, 2013). In addition, a number of reports concluded that various 5-HTR2A polymorphisms and suicidality were not associated (Li et al, 2006;De Luca et al, 2007;Fanous et al, 2009). This is in line with our findings as 5-HTR1A and 5-HTR2A polymorphisms were not associated with suicidal behaviour in our patient sample.…”
Section: Discussionsupporting
confidence: 94%
“…Analysis of the 5-HTR1A rs6295 variant produced no association with suicidal behaviour (González-Castro et al, 2013). In addition, a number of reports concluded that various 5-HTR2A polymorphisms and suicidality were not associated (Li et al, 2006;De Luca et al, 2007;Fanous et al, 2009). This is in line with our findings as 5-HTR1A and 5-HTR2A polymorphisms were not associated with suicidal behaviour in our patient sample.…”
Section: Discussionsupporting
confidence: 94%
“…A silencer element found downstream of the second promoter element suggests that HTR2A contains two alternative promoters (Myers et al, 2007; Serretti et al, 2007). Although almost 300 different SNPs within HTR2A have been listed (Fanous et al, 2009; Serretti et al, 2007) (Table 2), only a few are well-documented (Serretti et al, 2007): two silent mutations in the coding region, T102C and C516T (Spurlock et al, 1998);nine polymorphisms are located in the promoter region (Myers et al, 2007), the best-characterized of which is the A-1438G;five non-synonymous polymorphisms in the extracellular N terminal (polymorphism Thr25Asn), fourth transmembrane (lle197Val) and intracellular C terminal (Ser421Phe, Ala447Val, His452Tyr) regions (Davies et al, 2006). …”
Section: The Serotonergic System In Aggression and Suicidementioning
confidence: 99%
“…It should be mentioned, however, that other studies have failed to identify associations between genetic variants of 5-HT 2A and aggression in suicide victims (Videtic et al, 2006) and alcoholic patients (Preuss et al, 2000). Furthermore, most of the studies failed to find a significant association between T102C or His452Tyr and suicidal ideation (Bondy et al, 2000; Fanous et al, 2009; Preuss et al, 2000) suicide attempts (Arias et al, 2001; Correa et al, 2007; Etain et al, 2004; Giegling et al, 2006; Khait et al, 2005; Oswald et al, 2003; Preuss et al, 2000; Saiz et al, 2008; Tan et al, 2002; Zalsman et al, 2005; Zhang et al, 2008), severity of suicidal behaviour (De Luca et al, 2008a), suicide (Bondy et al, 2000; Crawford et al, 2000; Faludi et al, 2000; Ono et al, 2001), suicidal behaviour (Ertugrul et al, 2004; Murphy et al, 2011) or completed suicide (Turecki et al, 1999). Few studies found significant association between T102C CC genotype and suicide in suicide attempters compared to healthy control but not psychiatric controls (Vaquero-Lorenzo et al, 2009), or in depressed patients with suicide ideation (Du et al, 2000).…”
Section: The Serotonergic System In Aggression and Suicidementioning
confidence: 99%
“…Meta-analyses have reported an association between variants in the serotonin transporter [119] and the tryptophan hydroxylase 1 (TPH1) genes [120], although the latter was not associated within patient groups, suggesting that the association between the TPH1 genes and suicide behavior was confounded by association with the disease [121]. With regard to another frequently analyzed gene, the serotonin transporter 2A (HTR2A), there seems to be no firm evidence for an association [120,122]. In the area of less well-studied genes, a report analyzing patients with schizophrenia found an association between some genes involved in the HPA axis and suicidal behavior [123].…”
mentioning
confidence: 99%